Is Selfie Taking Behavior Beneficial for the Mental Wellbeing of Young Adults? (Dhaka University Journal of Biological Sciences, 2024)
The purpose of the present study was to investigate whether selfie taking behavior is beneficial for the mental well-being of young adults and to investigate the difference in psychological issues among people who like to take selfies and those who don’t. Two hundred participants were recruited in this study following convenience sampling technique. The Depression scale, Bangla version of the Self- Esteem scale, and Bangla version of the General Health Questionnaire -12 were used as instruments in this study. This study used t-test and Pearson Product Moment Correlation for analyzing data. Results showed that selfie taking behavior is negatively correlated with depression score which means more selfie taking leads to fewer depressive symptoms. It was also found that people who like to take selfies and post selfies more on social media have shown less depressive symptoms, better self-esteem and less psychological distress than the people who don’t like to take and post selfies. The results can be taken to indicate that people who like to take or post selfies more exhibit a better state of mental well-being and less psychological issues.Dhaka Univ. J. Biol. Sci. 33(2): 77-86, 2024 (July)